PERBANDINGAN PENGGUNAAN METODE PROBLEM BASED LEARNING DAN DIRECT INSTRUCTION DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS VI SD INPRES PARE’-PARE’ KEC. BAJENG KAB. GOWA - Riska Khusnul Mariyah; Muhammad Akhir; Ummu Khaltsum (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The purpose of this study was to compare the problem based learning and direct instructionmethods in teaching students' speaking skills in grade VI of SD Inpres Pare'-Pare'. Thebackground of this study is that students are less involved in learning Indonesian, especiallyspeaking skills, because the learning approach is dominated by lectures. The method usedin this study is a quantitative method. The results of the analysis show that the problem basedlearning method is more effective in improving students' speaking skills compared to thedirect instruction method. The t-test shows that the t-value obtained is 2,45 and the t-tablevalue at a significant level of 0.05 and df = n1 + n2 -2 = 38 is 2.02, because t-value > t-table(2,45 > 2.02) then reject H0. This shows a significant difference, in speaking skills with theproblem based learning method is better than the direct instruction method.